Exploring Differences in Attitudes of Nigerians Drivers Towards Road Safety Across Gender and Age - Etika, Anderson Aja (Transactions on Engineering and Computing Sciences, 2023)
The study present results from the partial adaptation of the Driver Attitude Questionnaire (DAQ) to examine road safety perceptions of a sample of Nigerian drivers. A total of 500 participants were sampled and completed self-reported questionnaires for the study, and drawn from local motor parks, workplaces, universities, and other gatherings within the urban areas of the cities of Calabar and Lagos. Findings from the study showed that, overall, across gender and age groups, non-use of Seatbelt, drink driving, speeding and mobile-phone usage were unacceptable behaviours. However, women were statistically more unaccepting to drink-driving and non-compliance of seatbelt wearing while driving than men. Also, younger drivers were more likely to report using mobile phones while driving than older drivers. The results of this study offer some practical suggestions in the development road safety interventions in Nigeria.